THE TEORETICAL FOUNDATIONS OF INVESTMENT SUPPORT FOR DIGITAL INTELLECTUALISATION OF ENGINEERING ENTERPRISES - VOVK, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is focused on the topical issues of digitalisation of the economy and its impact on the processes of formation and growth of intellectual capital. The author substantiates the deepening of the theoretical foundations of investment support and financial support for engineering enterprises in the processes of digital intellectualisation. The study used systematisation methods to summarise theoretical achievements in the theory of intellectualisation and its formation under the influence of trends in innovative development and conditions of the digital economy; methods of statistical analysis to analyse trends in investment; morphological analysis of scientific and information sources to study the forms and methods of investment support for intellectualisation; the method of retrospective analysis and visualisation of results to formalise the author's scientific positions. The author analyses the theoretical foundations and clarifies the interpretation of the concept of ‘digital intellectualisation’. Thus, digital intellectualisation should be based on the implementation of digital innovations and further formation of intellectual capital in the digital space, which ensures the sustainability of the enterprise's innovative development and the competitiveness of its engineering services. The article researches the forms of financing of investment activities in ensuring the continuity of digital intellectualisation. The author clarifies the peculiarities of financing digital intellectualisation in such forms as private financing, public financing, concession, joint-stock company, leasing. In particular, when making internal, own investments, engineering enterprises form the initial ownership of innovative digital technologies for consulting, which reduces the cost of technology and increases the profitability of engineering services. Also, investment mechanisms of state, foreign and venture capital financing of digital intellectualisation are attractive for engineering enterprises, as they allow them to master leading, competitive digital innovations. The author substantiates the sequence of influence of intellectualisation on the key characteristics of development of engineering enterprises.
Keywords: intellectualisation; investment; digital economy; financing; engineering sector; digital solutions; digital intellectualisation